Seeing crime, feeling crime: Visual evidence, emotions, and the prosecution of domestic violence - Moore, Dawn (Theoretical criminology, 2018)
Changes in prosecutorial strategies vis-a-vis domestic violence introduced new models of investigation that privilege images of victims. Drawing on case law, we argue these visual artefacts of victims' injuries as well as their videotaped sworn statements describing their assaults constitute what Haggerty and Ericson call a ‘data double', a virtual doppleganger who is meant to stand, often antagonistically in the stead of the flesh and blood victim. We further suggest, following theorizing on the emotional impact of images, that these pictures and videos, presented in court, have an emotional stickiness that differently affects both judges and juries as compared to the testimony of the flesh and blood victim. Thinking through temporality and notions of femininity we conclude that the truth effect of these images is that the victim's data double becomes more human than human, forcing us to rethink the relationships between victims, images, and the machinations of justice.